STATE-CREATIVE ACTIVITY OF UKRAINIAN RADICAL PARTY - Міщук, М. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted to the research the Ukraine Radical Party – Ukrainian Social-Radical Party one of most active in political respect parties’ in the social-political life of the Western Ukrainian land during the struggle of the Ukrainian people for winning sovereignty and independence in the 1918-1939 year. It is shown, that radical forces made a political life in the region more active and that all this time they defend the main aim of the nation which was the creation of the Ukrainian sovereign state.